ESTIMATION OF TRACE METAL CONTENTS IN LOCALLY-BAKED BREADS - Khalid, N.; Rehman, S. (The Nucleus, 2013)
In order to establish base line levels, estimation of some essential trace metals (Cu, Fe, Mn & Zn) has been conducted in four brands of fifteen locally baked breads of Rawalpindi /Islamabad area employing Atomic Absorption Spectrophotometry (AAS). The samples were digested in a mixture of nitric acid and perchloric acid and the analysis was done with air-acetylene flame. The reliability of the procedure employed was verify by analyzing Standard Reference Material, i.e., wheat flour (NBS-SRM-1567) for its Cu, Fe, Mn and Zn contents which were in good agreement with the certified values. The results revealed that brown breads contained higher amount of Fe 177.3 g g 1 and Zn 19.27 g g 1 while levels of Cu 21.90 g g 1 was found higher in the samples of plain bread. The determined metal concentrations in the bread samples were compared with the reported values for other countries. The effect of kneading/baking/slicing processes on the concentration levels of these metals was also studied. The daily intake of these metals through this source was calculated and compared with the recommended dietary allowance.